Opposite Effect of Cyclic Loading on the Material Properties of Medial Collateral Ligament at Different Temperatures: An Animal Study - Chen, Wentao; Zhou, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
In traffic accidents, the medial collateral ligament (MCL) injury of the knee joint of pedestrians is common. Biofidelic MCL material is important to realize its native biomechanics in simulations to clarify the injury mechanisms of pedestrians. Pedestrians’ MCLs usually experience cyclic loading at the intra-articular temperature of the knee joint before accidents. Temperature influences the material behaviors of ligaments. However, the mechanical properties of ligaments under cyclic loading have been widely evaluated only at room temperature rather than physiological temperature. Therefore, this study aimed to determine whether the difference between room and intra-articular temperatures influences the effect of cyclic loading on the mechanical properties of MCL. We measured the tensile properties of 34 porcine MCLs at room temperature (21-23℃) and intra-articular temperature (35-37℃), with either 10 cycles or 240 cycles of cyclic loading, a total of four different conditions. The structural responses and geometric data were recorded. After 240 cycles of cyclic loading, stiffness increased by 29.0% (p<0.01) at room temperature and decreased by 11.5% (p=0.106) at intra-articular temperature. Material properties were further compared because the geometric differences between samples were inevitable. At room temperature, after 240 cycles of cyclic loading, elastic modulus increased by 29.6% (p<0.001), and failure strain decreased by 20.4% (p<0.05). By contrast, at intra-articular temperature, after 240 cycles of cyclic loading, modulus decreased by 27.4% (p<0.001), and failure strain increased by 17.5% (p=0.193), insignificant though. In addition, there were no significant differences between the four groups in other structural or material properties. The results showed that temperature reversed the effect of cyclic loading on the mechanical properties of MCL, which may be caused by the high strength and thermally stable crosslinks of MCL. Therefore, for improving the fidelity of knee joint simulations and elucidating the injury mechanism of pedestrians, it is better to measure the mechanical properties of MCL at intra-articular temperature rather than room temperature.